FARMING INTEGRATED SYSTEM FOR ZERO WASTE SEBAGAI PEMBERDAYAAN MASYARAKAT DESA ALUE IE PUTEH KABUPATEN ACEH - Arico, Zulfan; Jayanthi, Sri; Putri, Kartika Aprilia; Nuraini, Nuraini (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The main problem found in Alue Ie Puteh Village is the large number of vacant land used as waste disposal sites; this is due to the lack of integrated waste management sites. This activity was carried out at the Village Hall by inviting elements of the surrounding community. The socialization and discussion of the Farming Integrated System For Zero Waste program cover the program as a whole; in this case it involves the process from the beginning to being sustainable. We the implementing team of the Biology Study Program, initiated a community service program as a program community empowerment through empowerment in utilizing organic and plastic waste to be applied to activities that include the manufacture of probiotics, the production of hydroponic devices, maggot cultivation and the manufacture of liquid organic fertilizers. Furthermore, these products used to support aquaponic cultivation assistance activities where hydroponic cultivation systems integrated with tilapia fish farming systems.